The impact of financial factors on the disclosure of corporate social responsibility - Rizqi, Reza Muhammad; Pratiwi, Aliah (Jurnal Inovasi Ekonomi, 2024)
The study empirically investigates the impact of financial factors, including profitability, leverage, and market capitalization, on the disclosure of corporate social responsibility (CSR). The research focuses on state-owned enterprises (SOEs) that are publicly traded on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The population consists of 77 SOEs, and a sample of 30 companies will be drawn using the purposive sampling technique based on specified criteria. Multiple linear regression analysis is employed for data analysis. The findings indicate that profitability, leverage, and market capitalization have a favorable and substantial influence on CSR disclosure. Consequently, this study provides theoretical validation for the application of stakeholder theory and legitimacy theory.